PENGARUH KOMPETENSI, SKEPTISISME PROFESIONAL, INTEGRITAS DAN OBJEKTIVITAS TERHADAP KUALITAS AUDIT - ANDRIANI, FITRI (Jurnal Akuntansi AKUNESA, 2017)
The aim of this study is to analyze at the effect of competence, professional skepticism, integrity and objectivity on audit quality. The research’s object is the Auditors of Public Accounting Firms in Surabaya, specificaly senior auditors, supervisors, managers and partners. Using questionnaires data collection and convenience sampling method, which the final samples are 18 Public Accounting Firms, this study finds that professional skepticism and integrity significantly affect audit quality. However, this study fails to prove that objectivity has significant affect on audit quality. Meanwhile this study could not analyze competence because based on validity test, the variable was not qualified. Keywords: Audit quality, Competence, Integrity, Objectivity, Professional Skepticism.   ..